DETERMINAN KEBIJAKAN DIVIDEND PERUSAHAAN NON KEUANGAN (Studi Bursa Efek Indonesia Tahun 2009-2013) - Sigit Widhicahyono, 1352020050; Sudiyatno, Bambang (Jurnal Mahasiswa Pasca Sarjana, 2015)
The objective of this study was to analyze the influence of current earnings, likuidity, profitabity, growth,Â institutional ownership,Â business risk to dividend payout ratio and control variable firm size . Overall, this study uses six independent variables: i.e. current earnings, likuidity, profitabity, growth,Â institutional ownership, riskÂ business, andÂ control variable firm sizein non-financial companies that is listed in Indonesian Stock Exchange over period 2009-2013. The sample was taken using the method of purposive sampling, and those meeting the selection criteria were also taken. The sample used was of 17 firms. The results of this research showed that growth,Â institutional ownershipdid not significantly effect to dividend policy. As for profitabilityearnings per share, likuidity, profitabity, business risk, firm sizehas significantly effect to dividend policy. The determination coefficient result showed 31,20 %. Thatâs about 31,20 % indicated the ability of the independent variables explained the dependent variable while 68,80 % explained by the other variables. Keywords: Current Earnings, Likuidity, Profitabity, Growth, Institutional Ownership, Business Risk, Dividend Payout Ratio and Firm Size